Decadal Variation in IOD Predictability During 1881–2016. Issue 23 (5th December 2018) - Song, Xunshu; Tang, Youmin; Chen, Dake
Abstract: In this study, a long‐term retrospective hindcast experiment is performed for the period from 1881 to 2016 with respect to tropical Pacific and Indian Oceans using a newly developed tropical intermediate coupled model. We focus on the predictability of the Indian Ocean Dipole (IOD) mode, especially its decadal variation. There is a considerable decadal variation in IOD predictability, with high skill after the 1980s and low skill in 1940–1960. This decadal variation is significant when the prediction target is observed in the boreal autumn and winter months. Further diagnostic analysis revealed that this decadal variation was primarily due to the decadal variation in the El Nino and Southern Oscillation (ENSO)‐IOD relation that characterized the ENSO‐induced precursor processes, strengthening the predictable IOD signal. Unlike the ENSO predictability that is substantially related to the ENSO signal, the IOD predictability is related to the ENSO‐induced signal rather than the total IOD signal. Plain Language Summary: Like the El Niño‐Southern Oscillation (ENSO) in the tropical Pacific Ocean, there is also a prominent air‐sea coupled climate mode of interannual variability, called Indian Ocean Dipole (IOD), characterized by an opposite sea surface temperature anomaly in the eastern and western Indian Ocean. IOD events can induce a series of climate anomalies in many areas of the world. However, the IOD prediction skill, evaluated by current climate models for the past 20–40 years, is very low and far behind that of ENSO. Thus, is it interesting and important to explore why the IOD prediction skill is low? Is its low skill due to a natural variation of predictability with decades? In this study, a long‐term retrospective hindcast experiment is performed for the period from 1881 to 2016 using a newly developed tropical intermediate coupled model, which, to the best of our knowledge, is the very first study investigating the IOD predictability for over 100 years. It was found that there is a considerable decadal variation in IOD predictability, with high skill after the 1980s and low skill in 1940–1960. Further diagnostic analysis revealed that this decadal variation was primarily due to the decadal variation in the ENSO‐IOD relation. Key Points: There is a considerable decadal variation in IOD predictability, with high skill after the 1980s and low skill in 1940–1960 This decadal variation of IOD predictability is significant when the prediction target is observed in the boreal autumn and winter months The decadal variation in IOD predictability was primarily due to the decadal variation in the ENSO‐IOD relation